Mapping Minds in Motion: A Scholarly Voyage and Evaluation of Research Trends and Patterns in Open Praxis - Aras Bozkurt; Hasan Uçar; Serpil Koçdar (Open Praxis)
This study offers a systematic and critical examination of the research trends, thematic patterns, and scholarly evolution of Open Praxis during the 2023–2024 publication period. Employing a multi-method approach that combines systematic review, bibliometric analysis, and data mining, the researchers analyzed a total of 81 articles indexed in the Web of Science database. The findings reveal significant growth in publication volume, an increasing trend toward multi-authored collaborations, and broad thematic diversification. Three dominant research themes were identified: (1) “Openness in Education,” reflecting macro-level engagements with open education, Open Educational Resources (OER), and Open Educational Practices (OEP); (2) “Technology-empowered Open and Distance Learning (ODL) Practices,” capturing the meso-level integration of digital technologies and online learning innovations; and (3) “Human-AI Symbiosis and AI-powered Education,” highlighting emerging micro-level discourses around artificial intelligence (AI), generative AI, and their implications for educational practice. The analysis also shows a strong association with the Sustainable Development Goal (SDG) of Quality Education (Goal 4), but limited engagement with other SDGs, pointing to a need for broader interdisciplinary attention. The study concludes that future directions should emphasize a more expansive, socially responsive, and critically engaged vision of openness to sustain the journal’s transformative role in the evolving landscape of open, distance, and flexible education.